Detailed carbon footprint of long-term care in an aging society - Narumi Kira; Sho Hata; Keisuke Nansai; Yosuke Shigetomi (Environmental Research Letters, 2025)
As the concept of planetary health garners increased attention, the necessity of quantifying the carbon footprint (CF) of healthcare supply chains has become more pronounced. Although global studies have examined the CF of the healthcare sector, there remains a notable gap in research concerning the CF of long-term care (LTC) services, which are essential to human health and welfare. We harmonized environmental input–output analysis with data derived from the national representative consumer-expenditure survey and LTC insurance statistics obtained from domestic economic and medical datasets to detail the CF of Japanese households requiring LTC. In Japan, the CF per capita associated with care was boosted as the care level increased. Notably, there is a disparity of up to 14 times between the care level with the lowest CF emissions and that with the highest CF emissions. Furthermore, households with LTC insurance demonstrate higher per-capita CF than those without such insurance, even when other household consumption needs are considered. This trend may mitigate the reduction in total CF related to household consumption, despite a national population decline, due to the anticipated rise in demand for LTC driven by an aging population by the year 2050 which is the target year for achieving carbon neutrality in Japan. Although renewable energy promotion represents an effective supply-side solution, a demand-side approach, such as the prevention of LTC, offers benefits for both climate change mitigation and human health.